Investigation of the impacts of the by-product of sewage treatment on some characteristics of maize in the early growth stage - Kaczur, Dávid; Moloi, Makoena Joyce; Takácsné , Mária Hájos; Tóth, Brigitta (Acta Agraria Debreceniensis, 2023)
The use of sewage sludge on arable land has been widespread for many years. This by-product, treated as waste, can provide valuable nutrients to the soil, but the applied amount of sewage sludge to arable land is limited. The possibility of application of sewage sludge is essentially determined by the composition of the sludge. The goal of the experiment was to demonstrate that the physiological, morphological, and biochemical parameters of maize (Zea mays L. cv. Armagnac) linearly change with increasing concentrations of sewage sludge (25%, 50%, and 75% as m/m%). The experiment was set up in a glasshouse. The following parameters were investigated: plant height, relative chlorophyll content, photosynthetic pigments (chlorophyll-a, chlorophyll-b, carotenoids), and leaf proline and malondialdehyde (MDA) content, and PS II quantum efficiency in the 3-leaf stages of the plants. Sewage sludge applied in lower doses had a beneficial effect on the initial growth of maize. The relative chlorophyll content was significantly higher in all treatments compared to the control. There was no significant difference in the maximum quantum efficiency of PS II reaction centers among the treatments. In this experiment, different concentrations of sewage sludge treatments had different impacts on the MDA and proline content of maize leaves. The proline content was significantly higher in all treatments, while the MDA content did not change significantly compared to the control.